Chemical characterization and anti-inflammatory activity of luteolin glycosides isolated from lemongrass - Vera Francisco (Journal of Functional Foods, 2014)
Flavonoids from lemongrass – Cymbopogon citratus (DC.) Stapf – leaves infusion, a commonly consumed beverage for the treatment of inflammatory-related conditions, were investigated in this work. Luteolin O-, C- and O,C-glycosides were isolated and identified by nuclear magnetic resonance, being the cassiaoccidentalin B structure fully characterized for the first time in lemongrass. The anti-inflammatory activity of luteolin and its glycosides was evaluated in lipopolysaccharide-stimulated macrophages. Luteolin glycosides demonstrated less cytotoxicity than luteolin itself. Although glycosylation decreases luteolin anti-inflammatory properties, being higher to C-glycosylation, an inhibitory effect on inflammatory mediator production (nitric oxide and IL-1β) was verified for the luteolin 7-O-β-glucopyranoside, without cytotoxic effects. Therefore, luteolin glycosides from lemongrass infusion are evidenced as a less toxic alternative to current anti-inflammatory drugs with promising use in pharmaceutical and food supplement industries. Additionally, this work establishes structure–activity relationships, which constitutes valuable information in the design of anti-inflammatory luteolin glycosides devoid of toxicity.